ANALISA PANJANG ANTRIAN DENGAN TUNDAAN PERSIMPANGAN BERSINYAL (STUDI KASUS PERSIMPANGAN PATAL-PUSRI) - Dharmayanto, Hapri; Ismail, Ismail (Jurnal Teknik Sipil, 2019)
the intersection of is one of the part of the thoroughfare that unite some streets around the stadium and connecting some streets around the stadium to the point where it is a region happened quite a lot though the whole range of the movement of vehicles who end up creating long queues and exceptionally large, This situation is commonly known term traffic congestion.Research that we do is analysis long his line with tundaan at a crossroads bersinyal with four phase, The roads are the type 4 2 d and 4 / / was 2 .The method of calculation used manual kapaitas ( mkji indonesia s road , 1997 ) . The implementation of the was conducted over 2 ( two the day the day the day monday and tuesday, on the day! april 2018.A method of analysis the intersection of conducted from geometry simpang, volume traffic, environmental conditions, and class obstacles side.The results of the study obtained wide pendekat the north and south 7.50 meters, and the east and west 9.50 meters. Volume traffic at the junction as pendekat north the way of r.Abdul rojak of 2450 kend per hour, pendekat the east the way akbp check agus of 3401 kend per hour, the south the way of r.Soekamto of 2469 kend per hour and jalan mp mangku a country as large 5174 kend per hour.Long his line the north of 2576 smp / hours, the east of 2368 smp / hours, the south of 4708 smp / hours and the west of 4891 kend per hour. To know the intersection of service levels seen from large .As for the value of exceptionally large in a northern direction 21,43 sec / smp , 19.75 sec / smp, east , south 17,94 sec / smp and the west 20,87 sec / smp.Category b it means good service levels .